Four recurrent miscarriages – Is it a case of antiphospholipid syndrome? - Roop Kishore, Yashdev Atri; Shalihin, Mohd Shaiful Ehsan (2024)
Introduction: Antiphospholipid syndrome (APLS) is usually clinically suspected in antenatal women presented with recurrent miscarriages. Screening is usually conducted, especially for those with persistent, unexplained recurrent miscarriages in the first trimester. However, most patients might not seek medical attention earlier, causing a delay in screening. Nevertheless, it is a dilemma for patients with recurrent miscarriages, especially up to four miscarriages, to be presumed as APLS until proven otherwise. Case: We reported a 37-year-old Gravida 5 Para 0+4 at four weeks of amenorrhoea presented with one episode of per vaginal bleeding. APLS and other relevant causative screenings had been performed, and the results were normal. Surprisingly, her pregnancy is still viable and progressing well. Discussion: This case proved that recurrent miscarriages on more than three occasions are not always equivalent to antiphospholipid syndrome. The underlying cause can be idiopathic or other causes that have not been investigated yet, including the possibility of a congenital anomaly. Conclusion: Suspicion of APLS is warranted and should be verified with the gold standard screening tests. In any case, where the results were normal, further assessments such as uterine evaluation, infectious disease screening, and pathological examination should be considered. Pre-pregnancy screening should be a minimal requirement for all women of reproductive age for the evaluation and prevention of similar outcomes to those of other women.